Morphology and expression of genes related to skeletal muscle growth in juveniles of pirarucu (Arapaima gigas, Arapaimatidae, Teleostei) - doi: 10.4025/actascianimsci.v35i3.18219 - Carani, Fernanda Regina; Duran, Bruno Oliveira da Silva; Paula, Tassiana Gutierrez de; Piedade, Warlen Pereira; Dal-Pai, Maeli (Acta Scientiarum. Animal Sciences, 2013)
Skeletal muscle growth in the pirarucu (Arapaima gigas) is highly interesting to fish farmers because it provides information about how the mechanism in muscle mass increase, characteristic of the species, is regulated. Pirarucu has specific muscle growth that highlights the species’s significance and commercial value. Current research evaluates the morphology and the growth-related gene expression in the red and white skeletal muscles of the pirarucu. Muscle samples were collected from the lateral anterior region and frozen in liquid nitrogen. Histological sections were performed and stained by HE for morphological analysis. Red and white muscle samples were used to determine MyoD, myogenin, and myostatin genes expression by Real-time Polymerase Chain Reaction. Although MyoD and myogenin were not statistically different in the two types of muscles, myostatin was significantly higher in the white rather than in the red muscle. Results show the muscle growth characteristics of the species and may be helpful for improving aquaculture management programs.